Comparison of fully-automated radiosyntheses of [11C]erlotinib for preclinical and clinical use starting from in target produced [11C]CO2 or [11C]CH4 - Cécile Philippe; Severin Mairinger; Verena Pichler; Johann Stanek; Lukas Nics; Markus Mitterhauser; Marcus Hacker; Thomas Wanek; Oliver Langer; Wolfgang Wadsak (SpringerOpen, 2018)
Abstract Background [11C]erlotinib has been proposed as a PET tracer to visualize the mutational status of the epidermal growth factor receptor (EGFR) in cancer patients. For clinical use, a stable, reproducible and high-yielding radiosynthesis method is a prerequisite. In this work, two production schemes for [11C]erlotinib applied in a set of preclinical and clinical studies, starting from either [11C]CH4 or [11C]CO2, are presented and compared in terms of radiochemical yields, molar activities and overall synthesis time. In addition, a time-efficient RP-HPLC method for quality control is presented, which requires not more than 1 min. Results [11C]erlotinib was reliably produced applying both methods with decay-corrected radiochemical yields of 13.4 ± 6.2% and 16.1 ± 4.9% starting from in-target produced [11C]CO2 and [11C]CH4, respectively. Irradiation time for the production of [11C]CO2 was higher in order to afford final product amounts sufficient for patient application. Overall synthesis time was comparable, mostly attributable to adaptions in the semi-preparative HPLC protocol. Molar activities were 1.8-fold higher for the method starting from [11C]CH4 (157 ± 68 versus 88 ± 57 GBq/μmol at the end of synthesis). Conclusions This study compared two synthetic protocols for the production of [11C]erlotinib with in-target produced [11C]CO2 or [11C]CH4. Both methods reliably yielded sufficiently high product amounts for preclinical and clinical use.